Preparation and photoluminescence performance of BaMoO4:Sm3+ orange–red phosphor. Issue 1 (26th October 2022) - Zhao, Li; Jing, Cao; Ya-nan, Wang; Kun-yao, Wu; Yong-feng, Wang; Lu, Deng
Abstract: In the present paper, orange–red BaMoO4 :Sm 3+ phosphor was synthesized by high-temperature solid-phase method. The morphology, elemental composition, crystal structure, photoluminescence performance, and charge compensation mechanism of BaMoO4 :Sm 3+ were investigated. Results indicated that the BaMoO4 :Sm 3+ phosphor particles were spherical-like in shape with approximate particle size of 2 μm and contained Ba, Mo, O, and Sm elements. The Rietveld-refinement of X-ray diffraction profile of BaMoO4 :Sm 3+ was consistent with a tetragonal lattice. Under 404 nm excitation of light, BaMoO4 :Sm 3+ phosphor showed the strongest emission peak at 649 nm and emitted an orange–red light. When the orange–red phosphor was packaged with a 395 nm UV chip and tested, the color coordinates were (0.3109, 0.3626) under a current of 60 mA, the color rendering index R a = 81.5, and the color temperature was 6385 K. These results indicated that BaMoO4 :Sm 3+ red phosphor is suitable as a red light component in WLEDs and has potential practical applications.